An assessment of the key construct of the Integrated Cognitive Antisocial Potential (ICAP) theory: psychometric qualities of the antisocial attitudes scale among a sample of Portuguese adolescents - Gomes, Hugo Miguel Santos (2023)
Antisocial Potential is the key construct of the Integrated Cognitive Antisocial Potential (ICAP) theory, and it has been measured by the antisocial attitude (AA) scale. The ICAP theory is one of the main theoretical frameworks in developmental and life-course criminology. The present study aimed to examine the psychometric properties of the AA scale in the Portuguese adolescent population. Our sample was comprised of 485 participants. The Portuguese version of the AA scale was demonstrated to be a reliable and valid measure of antisocial potential. This is the first study exploring the AA scale outside of the scope of the CSDD and it reveals antisocial potential as a strong predictor of criminal behavior that should be considered in future research.